2014
DOI: 10.1371/journal.pone.0105499
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Depression and Diabetes in the Community: Do Symptom Dimensions Matter? Results from the Gutenberg Health Study

Abstract: ObjectivesWhile a bidirectional relationship between diabetes and depression has been established, there is little knowledge if the associations are due to somatic-affective or cognitive-affective dimensions of depression.Research Design and MethodsIn a population-based, representative survey of 15.010 participants we therefore studied the associations of the two dimensions of depression with diabetes and health care utilization among depressed and diabetic participants. Depression was assessed by the Patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 33 publications
1
23
0
3
Order By: Relevance
“…For example, a study of adults with type 2 diabetes showed that much of the overidentification of depression by a commonly used screening instrument (14) was explained by symptoms involving impairments in sleep, appetite, and energy level (15). Results from a large, population-based study showed that differences in depressive symptoms between adults with and without diabetes were limited to somatic symptoms; no significant differences were found for cognitive-affective symptoms of depression (16). Further, qualitative analysis of structured clinical interviews for depression showed that patients with type 2 diabetes often discuss somatic symptoms of depression as being caused by diabetes and diabetes-related medications (17).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study of adults with type 2 diabetes showed that much of the overidentification of depression by a commonly used screening instrument (14) was explained by symptoms involving impairments in sleep, appetite, and energy level (15). Results from a large, population-based study showed that differences in depressive symptoms between adults with and without diabetes were limited to somatic symptoms; no significant differences were found for cognitive-affective symptoms of depression (16). Further, qualitative analysis of structured clinical interviews for depression showed that patients with type 2 diabetes often discuss somatic symptoms of depression as being caused by diabetes and diabetes-related medications (17).…”
Section: Introductionmentioning
confidence: 99%
“…Many other non-psychiatric medical conditions associate with increased levels of depression, including obesity [42], type II diabetes [43], cardiovascular disease [44], chronic obstructive pulmonary disorder [45], non-alcoholic fatty liver disease (NAFLD) [46] and a variety of different cancers [47,48]. As with depressionassociated psychiatric conditions, the increased rates of depression in general medical inflammatory conditions have classically been attributed to a psychological reaction to an often long-term, chronic condition.…”
Section: Depression and Other Inflammatory Conditionsmentioning
confidence: 99%
“…Os pacientes diabéticos sofrem de sintomas significativamente mais introversivos do que pessoas saudáveis, especialmente sintomas somáticos, perturbação do sono, compulsões e humor depressivo 51 . As discussões mais recentes sugerem que alterações metabólicas do diabetes, somadas à condição inflamatória da doença, podem estar relacionadas aos sintomas somático-afetivos da depressão, como distúrbios do sono, mudança de apetite, fadiga e problemas psicomotores 52 . Sabe-se que pessoas com diabetes correm um risco substancialmente aumentado de experimentar angústia mental, particularmente depressão 53 .…”
Section: Depressão Relacionada à Encefalopatia Diabéticaunclassified
“…Sabe-se que pessoas com diabetes correm um risco substancialmente aumentado de experimentar angústia mental, particularmente depressão 53 . Além disso, um crescente conjunto de evidências indicam uma relação bidirecional entre essas duas condições 52,54 . No entanto, a depressão muitas vezes é subdiagnosticada em pessoas com diabetes 55 56 .…”
Section: Depressão Relacionada à Encefalopatia Diabéticaunclassified